Dependence of the Ukrainian Economy on Foreign Capital - Medentseva, M.M. (Економічний вісник Донбасу, 2014)
The article gives a clear picture of the foreign capital operation in Ukraine. The investment attractiveness of Ukraine was defined. The analysis of elasticity and correlation and regression analysis were carried out to determine the level of Ukrainian economy’s dependence on the foreign capital. The multivariate correlation analysis was carried out to find out the factors of influence on foreign direct investment inflow in Ukraine. У статті розглянуто функціонування іноземного капіталу в Україні. Дана оцінка інвестиційної привабливості України. Проведено аналіз еластичності і кореляційно-регресійний аналіз для визначення ступеня залежності української економіки від іноземного капіталу. Проведено багатофакторний кореляційний аналіз для визначення факторів впливу на обсяги прямих іноземний інвестицій в Україну. В статье рассмотрено функционирование иностранного капитала в Украине. Дана оценка инвестиционной привлекательности Украины. Проведен анализ эластичности и корреляционно-регрессионный анализ для определения степени зависимости украинской экономики от иностранного капитала. Проведен многофакторный корреляционный анализ для определения факторов влияния на объемы прямых иностранный инвестиций в Украину.